1, 2 Timothy, Titus - Lea, Thomas D; Griffin, Hayne P. (Nashville, TN Broadman, 1992)
Includes bibliographical references and indexes.
Keywords: Bible. N.T. Timothy -- commentaries; Bible. N.T. Titus -- commentaries